(untitled) (Sound Stage Screen, 2023)
This article examines the process of developing a posthuman opera, Michel van der Aa’s Upload (2021), from the perspective of a rehearsal ethnography. Proposing a rehearsal-oriented ontology of opera, this article avoids discussions of the performance and even the music itself to focus on stages of rehearsing with a virtual body. As a participant-observer, I examine how the rehearsal space of Upload evolves into a laboratory that negotiates receptacles of digital data with congenital bodies. Dissecting the avatar as a compound of (non)human agents, I interrogate how rehearsing a virtual body reconfigures operatic production dynamics. The operatic rehearsal processes repetition and connection, and co-evolves together with the technologies of production. With the example of various agents’ interactions during the rehearsal, I illustrate how the figure of the avatar reproduces Upload out of canonical rehearsal practices by recalibrating the connections between opera’s agents. These elaborations lead to an understanding of van der Aa as a composer who recalibrates himself into the posthuman form of an opera production.